SISTEM JARINGAN TRANSPORTASI LOGISTIK KAWASAN PERBATASAN PROVINSI PAPUA DENGAN PAPUA NEW GUINEA - Semuel Rorrong Daturatte; Muhammad Yamin Jinca; Shirly Wunas (Jurnal Transportasi, 2010)
The number of residents who live in the border area of the province of Papua and the Country of Papua New Guinea (PNG) is 129,835 persons or 4.6% of the total population of Papua. Some of these settlements are still isolated and far behind in terms of education, health, and economic and their economic conditions are still below the poverty line. Government efforts to raise living standards through the provision of logistical needs of border communities are still hampered by the difficulty of accessibility that exists in the area. The results of this study indicate that the logistic needs of border communities have not been evenly distributed, and this is not caused by the lack of integration among transportation modes alone. The problems include thelogistics needs which are stopped at one of the modes of service, the occurrence of damage, and goods needed by people do not reach the border areas where the people live. To address these problems, there is a need for strategies and policies to deal with the transportation network system to distribute needed logisticsby optimizing existing transportation infrastructure, accelerating and improving the transportation infrastructure, improving inter-modal coordination, and improving management of transportation logistics.Keywords: border areas, transportation networks, inter-modal coordination, logistics management